Rancang Bangun Aplikasi Sistem Informasi Geografis untuk Pencarian Bengkel Resmi Honda di Kota Depok Berbasis Android dengan Metode Location-Based Service (LBS) - Farhan; NM Faizah; Lucky Koryanto (Design Journal, 2024)
For modern society, motor vehicles have become the main mode of transportation. Regular vehicle maintenance is very important to maintain its performance and ensure safety while driving. However, many people have difficulty finding the nearest authorized Honda repair shop. The purpose of this study is to produce an android-based application that will help users find authorized Honda repair shops using the Location Based Service (LBS) method. This application will help find repair shops, check the accuracy of the repair shop location, and help raise awareness of the need to service vehicles at authorized repair shops. System development process Extreme programming consists of planning, designing, coding, and testing stages. The APP was developed from Android studio, Google Firebase, GPS, LBS. The test results show that this application can help users find the nearest authorized Honda repair shop, provide accurate address information, working hours, and repair shop contacts. This application also provides booking and navigation services to the repair shop. By using LBS, customers can contact the repair shop without having to waste time looking for the repair shop location first. This application is expected to increase the loyalty of Honda motorcycle owners to use authorized Honda repair shop services and increase awareness of the importance of routine vehicle maintenance